Asymptotic and Numerical Methods in Estimating Eigenvalues - YILMAZ, BÜLENT (HINDAWI LTD, 2013)
Asymptotic formulas and numerical estimations for eigenvalues of SturmLiouville problems having singular potential functions, with Dirichlet boundary conditions, are obtained. This study gives a comparison between the eigenvalues obtained by the asymptotic and the numerical methods.
Keywords: FINITE-DIFFERENCE METHOD; BOUNDARY-VALUE; APPROXIMATIONS; EXPANSION